A lengyel államiság visszaszerzésének napja: Varsó 1918. november 11. - Tefner, Zoltán (Acta Scientiarum Socialium, 2018)
The biggest celebration of Poland is linked to the beginning of November and the end of the war. In Eastern Europe the successor states of the Austrian – Hungarian Monarchy only differ from the formation of the Polish State that the latter didn’t impregnate in big mass movements. The Polish arbitrarily created a historical milestone dedicating their celebration day to the arrival of Pitsudski in Warsaw. Pitsudski arrived in Poland from his Magdeburg’s imprisonment, and started to organise the Polish state. This wasn’t a one-day action, but the process lasted for months since the summer of 1917. Pitsudski was appointed to the commander-in-chief of the army, then later he became the head of state. In the autumn of 1918 until the December of that year, thanks to the dramatic organising activity, which was full of conflicts, Poland had got an own government. This achievement was owed to the fact that Pitsudski was the only politician who was accepted the by each class of the Polish society and that’s why the country avoided the anarchy for which it had big a chance.